2012
DOI: 10.3233/jad-2012-120637
|View full text |Cite
|
Sign up to set email alerts
|

Validation of AclarusDx™, a Blood-Based Transcriptomic Signature for the Diagnosis of Alzheimer's Disease

Abstract: Biomarkers have gained an increased importance in the past years in helping physicians to diagnose Alzheimer's disease (AD). This study was designed to identify a blood-based, transcriptomic signature that can differentiate AD patients from control subjects. The performance of the signature was then evaluated for robustness in an independent blinded sample population. RNA was extracted from 177 blood samples (90 AD patients and 87 controls) and gene expression profiles were generated using the human Genome-Wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 57 publications
1
32
0
1
Order By: Relevance
“…This suggests that these processes not only are affected in brain tissue but also are reflected in a systemic response that can be detected using gene expression in blood. This is also well in agreement with similar findings in previous AD studies [34][35][36][37][38]. The results also support the concept of AD as a multifactorial sporadic disorder [54] with multiple genes and alterations in gene expression involved [55,56].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This suggests that these processes not only are affected in brain tissue but also are reflected in a systemic response that can be detected using gene expression in blood. This is also well in agreement with similar findings in previous AD studies [34][35][36][37][38]. The results also support the concept of AD as a multifactorial sporadic disorder [54] with multiple genes and alterations in gene expression involved [55,56].…”
Section: Discussionsupporting
confidence: 82%
“…We and others have previously shown that disease biomarkers to classify AD with dementia from cognitively healthy individuals are present in blood [16,23,35] and an algorithm based on the gene expression of a selected set of genes can be used to identify those with an AD dementia [34][35][36]. We have now further extended these findings to also include AD in the pre-dementia stage of the disease.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, application of Polymerase Chain Reaction (PCR) has proposed circulating microRNAs (Kumar et al, 2013;Tan et al, 2014); the most promising result showed a panel of 12 microRNAs which differentiated AD from controls with accuracy of 93% (Leidinger et al, 2013). Transcriptomic tests have also been applied on blood; a signature consisting of 170 probe sets has been identified to discriminate AD from controls with sensitivity and specificity of 81.3% and 67.1% respectively (Fehlbaum-Beurdeley et al, 2012).…”
Section: Current Markers Of Admentioning
confidence: 99%
“…Various studies [15,16,44,45,46,47] have shown that the gene expression blood test can aid in the diagnosis of mild to moderate AD. As for the other high-throughput approaches, further confirmation based on independent cohorts is required.…”
Section: Circulating Biomarker Signaturementioning
confidence: 99%